Comparative environmental life-cycle analysis of concretes using biomass and coal fly ashes as partial cement replacement material - Teixeira, E. R. (2016)
Nowadays, the concrete production sector is challenged by attempts to minimize the usage of raw materials and energy consumption, as well as by environmental concerns. Therefore, it is necessary to choose better options, e.g. new technologies or materials with improved life-cycle performance. One solution for using resources in an efficient manner is to close the materials' loop through the recycling of materials that result either from the end-of-life of products or from being the by-product of an industrial process. It is well known that the production of Portland cement, one of the materials most used in the construction sector, has a significant contribution to the environmental impacts, mainly related with carbon dioxide emission. Therefore, the study and utilization of by-products or wastes usable as cement replacement in concrete can supply more sustainable options, provided that these type of concrete produced has same durability and equivalent quality properties as standard concrete. This work studied the environmental benefits of incorporating different percentages of two types of fly ashes that can be used in concrete as cement replacement. These ashes are waste products of power and heat production sectors using coal or biomass as fuels. The results showed that both ashes provide a benefit for the concrete production both in terms of environmental impact minimization and a better environmental performance through an increase in cement replacement. It is possible to verify that the incorporation of fly ashes is a sustainable option for cement substitution and a possible path to improve the environmental performance of the concrete industry.